Характеристика основних напрямів наукової діяльності Миколи Юхимови ча Чижова як теоретика права - Дзевелюк, Андрій Володимирович; Дзевелюк, Андрей Владимирович; Dzeveljuk, Andrej (Одеса : Юрид. л-ра, 2012)
This article explores the main directions of scientific activity of Nikolai Efimovich Chizhov: general study of law, historical trend of studies, research of scientific, theoretical and methodological problems of legal science, educational and methodical direction of their activity, and explanation.
Дзевелюк А. В. Характеристика основних напрямів наукової діяльності Миколи Юхимови ча Чижова як теоретика права / А. В. Дзевелюк // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 273-279.
Keywords: М. Ю. Чижов; теорія права; історія права; методологія права; Н. Е. Чижов; теория права; история права; методология права; M. Y. Chyzhov; theory of law; history of law; methodology of law